Loop diuretics in adult intensive care patients with fluid overload: A protocol for a systematic review of randomised clinical trials with meta‐analysis and Trial Sequential Analysis. Issue 9 (15th July 2020) - Wichmann, Sine; Barbateskovic, Marija; Lindschou, Jane; Gluud, Christian; Perner, Anders; Bestle, Morten H.
Abstract : Background: In the intensive care unit, fluid overload is frequent and a risk factor for organ dysfunction and increased mortality. Primarily, lung and kidney functions may be impaired by fluid overload resulting in acute respiratory failure and acute kidney injury. No clinical guidelines exist for treatment of fluid overload in intensive care patients. Loop diuretics, most often furosemide, appear to be the most frequently used pharmacological intervention. The aim of this protocol is to describe the methods of a systematic review assessing the evidence of treatment with loop diuretics in adult intensive care patients with fluid overload. Methods: We will conduct a systematic review with meta‐analysis and report it according to Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) Statements, use the recommendations of the Cochrane Handbook and assess the quality of the evidence using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. We will include randomised clinical trials identified through searches of major international databases and trial registers. Two authors will independently screen and select trials for inclusion, extract data and assess the methodological quality using the Cochrane risk of bias tool. Extracted data will be analysed using Review Manager and Trial Sequential Analysis. The protocol is registered at PROSPERO. Discussion: We aim to provide reliable evidence on the use of loop diuretics in adult intensive care patients with fluid overload to guide clinicians, decision makers and trialists on clinical practice.